Interpretasi Batuan Bawah Permukaan Prospek Bijih Besi di Kawasan Desa Pagubugan dan Desa Pagubugan Kulon Kecamatan Binangun Kabupaten Cilacap Berdasarkan Survei Magnetik: Adib Meiditha Wibowo, Sehah, dan Sugito - Adib Meiditha Wibowo Adib Meiditha Wibowo; Sehah Sehah; Sugito Sugito (Jurnal Fisika dan Aplikasinya, 2019)
Geophysical exploration to determine the potential of iron sand in the Pagubugan Village and Pagubugan Kulon Village areas, District of Binangun, Regency of Cilacap has been carried out from May to August 2018 using the magnetic method. The acquisition of magnetic data has been done in the research area at the geographical position stretching from 109.29880 E to 109.318920 E and 7.684300 S to 7.704020 S. Morphologically, the research location is the part of the eastern coastal in the district of Binangun. The results of the modeling and interpretation of magnetic anomaly data that obtained indicate the presence of rock deposite which thought to contain iron ore which intersects with clay, silt, sand, gravel, and crust from the Alluvium formation with a magnetic susceptibility value of 0.0094 cgs units. This rock deposite is estimated to lie at a depth of 0 to 53 meters and stretches at the geographical position from 109.309810 E and 7.69264 S to 109.31787 E and 7.695750 S.